Monitor and evaluation of food management for COVID-19 patients at the central isolation shelter in Sleman Regency, Yogyakarta - Amalliyah, Puji; Rahmawati, Vista Ari; Arjuna, Tony (BKM Public Health and Community Medicine, 2021)
Background: The COVID-19 outbreak hit the world starting at the end of 2019 and spread to Indonesia in the first quarter of 2020. As of early November 2021, the Center for Systems Science and Engineering (CSSE) at Johns Hopkins University (JHU) COVID-19 Data and Our World In Data showed 4.25 million cases with 143 thousand deaths in Indonesia. When the number of COVID-19 cases was very high, the Indonesian government gave instructions to establish centralized isolation shelters in each area by utilizing hajj dormitory facilities, village halls, and government buildings. The Tagana Public Kitchen was responsible for patient and shelter staff food management in Sleman Regency under the Social Service supervision. Content: The Tagana Public Kitchen Sleman served food needs for patients and staff at three centralized isolation shelters in Sleman. The isolation shelters were Yogyakarta Hajj Dormitory (Sinduadi), Rusunawa Gemawang (Sinduadi), and Universitas Islam Indonesia (UII) shelter (Umbulmartani). Interviews with kitchen managers found no significant obstacles in providing food for patients in isolation shelters. However, after being observed, the current state of the Tagana Sleman Public Kitchen was not yet standardized, especially in the layout of the kitchen, completeness of facilities, and sanitation hygiene. These were very important to improve because the consumers served were Covid-19 patients. Although the patient had quite good satisfaction with food management, as shown in the survey result, there were still suggestions for improving food variety and temperature. The challenge of improving this standard was budget. Based on the current menu analysis results, the diet provided had not met the patient's nutritional needs because they should follow the TKTP (High-Calorie High Protein) diet of 2200-2400 kcal. In budget calculations, if the menu is improved and follows the diet, the current budget of IDR 15,000/per person/per meal is not sufficient. Likewise, repairing kitchen facilities will undoubtedly require more funds. Latar belakang: Wabah COVID-19 telah melanda dunia mulai akhir tahun 2019 dan mulai menyebar ke Indonesia di triwulan pertama tahun 2020. Terhitung sampai awal November 2021 berdasarkan data dari JHU CSSE COVID-19 Data dan Our World In Data, jumlah kasus di Indonesia tercatat 4,25 juta dengan 143 ribu meninggal dunia. Pada saat jumlah kasus COVID-19 sangat tinggi, Pemerintah Indonesia memberikan instruksi untuk membentuk shelter isolasi terpusat di masing-masing daerah dengan memanfaatkan fasilitas asrama haji, balai desa, gedung pemerintah, dan sebagainya. Pelayanan makanan untuk pasien dan petugas shelter di Kabupaten Sleman dikelola oleh Dapur Umum Tagana yang berada dalam pengawasan Dinas Sosial. Konten: Dapur Umum Tagana Sleman berada di Tridadi, Sleman. Setiap harinya saat ini melayani kebutuhan makan untuk pasien dan petugas di 3 shelter isolasi terpusat (isoter) Sleman. Isoter tersebut adalah Asrama Haji Yogyakarta (Sinduadi), Rusunawa Gemawang (Sinduadi), dan shelter UII (Umbulmartani). Wawancara dengan pengelola dapur, tidak ditemukan kendala yang berarti selama penyelenggaraan makanan untuk pasien di isoter. Namun setelah diobservasi, keadaan Dapur Umum Tagana Sleman saat ini belum terstandar terutama tata letak dapur, kelengkapan fasilitas, dan higine sanitasi. Hal tersebut tentu sangat penting untuk diperbaiki karena konsumen yang dilayani adalah pasien Covid-19 yang notabennya sangat butuh perlakuan khusus. Walaupun dari hasil survei kepuasan pasien terhadap pelayanan makanan ditemukan hasil yang cukup baik, tetapi masih ada masukan untuk perbaikan variasi makanan dan suhu makanan. Tantangan dari perbaikan standar ini adalah anggaran. Berdasarkan hasil analisis menggunakan menu saat ini, kebutuhan gizi pasien belum terpenuhi karena seharusnya mengikuti diet TKTP (Tinggi Kalori Tinggi protein) 2200-2400 kkal. Dalam perhitungan anggaran jika menu diperbaiki dan sesuai dengan diet maka anggaran Rp15.000,-/per orang/per sekali makan saat ini tidak mencukupi. Begitu juga dengan perbaikan fasilitas dapur tentunya akan membutuhkan dana lebih.